Forensic Service Supply by Audit Firms: Classification, Market, Methods, and Prior Research - Quick, Reiner (My University, 2017)
Provision of non-audit services is of increasing economic importance for audit firms Especially provision to non-audit clients Wide range of offered services From detection to prevention, from bribery to fraud to violation of code of conduct Small, but growing market with Big 4 as clear leaders Wide variety of backgrounds of forensic services professionals Consequently, diverse portfolio of methods Most research focuses on fraud with some high-quality publications Missing high-quality forensic services research
Keywords: Auditoría; Audit; Forensic; Firm